Sulfur-Rich Ageing Mechanism of Silicone Encapsulant Used in LED Packaging: An Experimental and Molecular Dynamic Simulation Study - Chen, Wei; Chen, Ye; Cao, Yixing; Cui, Zhen; Fan, Xuejun; Zhang, Guoqi; Fan, Jiajie (Frontiers in Materials, 2022)
In a light-emitting diode (LED) package, silicone encapsulant serves as chip protector and enables the light to transmit, since it exhibits the advantages of high light transmittance, high refractive index, and high thermal stability. However, its reliability is still challenged under harsh operation conditions. In this study, the optical and mechanical properties of silicone encapsulant, including appearance, light transmittance, Young's modulus and tensile strength, were experimentally monitored during the sulfur-rich ageing process. Meanwhile, the Fourier Transform Infrared (FTIR) spectroscopy and Molecular Dynamics (MD) simulation were used to reveal its degradation mechanism. The results show that: (1) In the sulfur (S8)-rich ageing process, the severe vulcanization occurred in silicone encapsulant only assisted by the high temperature and high moisture, as the existence of H2S from the reaction of S8 and H2O vapor. (2) Vulcanization characterized by the formation of sulfhydryl (-SH) group lowered both the optical and mechanical properties of silicone encapsulant; (3) Hydrolysis reaction featured by the formation of hydroxyl (-OH) group decreased the mechanical performances of silicone encapsulant, but brought slight harm to its optical performances.